Cannabis use during methadone maintenance treatment for opioid use disorder: a systematic review and meta-analysis - McBrien, Heather (CMAJ Open, 2019)
BACKGROUND: Rates of cannabis use among patients receiving methadone maintenance therapy are high, and cannabis use may be associated with outcomes of methadone maintenance therapy. We examined the effect of cannabis use on opioid use in patients receiving methadone maintenance therapy to test the hypothesis that cannabis use is associated with a reduction in opioid use. METHODS: In this systematic review, we searched MEDLINE/PubMed, Embase, PsycINFO, CINAHL and ProQuest Dissertations and Theses Global from inception to July 12, 2018. We summarized the effects of cannabis use on opioid use during methadone maintenance therapy and treatment retention. We conducted meta-analyses using a random effects model. RESULTS: We included 23 studies in our review. We performed a meta-analysis of 6 studies, with a total number of participants of 3676, examining use of cannabis and opioids during methadone maintenance therapy. Owing to high heterogeneity, we described the studies qualitatively but provide the forest plots as supplemental material. The overall quality of evidence was very low, with a high risk of bias, owing to the nature of observational studies. INTERPRETATION: We found no consensus among studies that cannabis use is associated with reduced opioid use or longer treatment retention when used during methadone maintenance therapy in patients with opioid use disorder. PROSPERO Registration: CRD42015029372